2017
DOI: 10.3390/fishes2040017
|View full text |Cite
|
Sign up to set email alerts
|

Chlorella vulgaris as Protein Source in the Diets of African Catfish Clarias gariepinus

Abstract: Plant proteins substitutes of fishmeal in aquafeed are usually lacking in some essential amino acids and fatty acids. The microalgae Chlorella vulgaris has good-quality protein with amino acids rich in methionine, lysine and alanine. Four novel diets having C. vulgaris as the main source of protein were produced for African catfish Clarias gariepinus with an initial average weight of 1.09 ± 0.05 g. The diets were labeled Feed 1 (F1) to feed 4 (F4). The treatment diets were included 25% (F1), 15% (F2), 5% (F3) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
8
2
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 44 publications
4
8
2
2
Order By: Relevance
“…The identified amino acids, fatty acids and some of the lipids via LCMS agree with recently published results [ 47 , 48 ].…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…The identified amino acids, fatty acids and some of the lipids via LCMS agree with recently published results [ 47 , 48 ].…”
Section: Resultssupporting
confidence: 90%
“…The growth medium was adjusted and monitored at pH 7.5. The wet crude product was harvested via centrifugation by employing high-speed Sorvall Evolution RC centrifuge (Thermo Electron Corporation, Asheville, NC, USA) at 12,000 rpm at 25 °C, kept at −80°C for five days, and lyophilized using a freeze drier [ 48 ]. Solvent extraction was carried out with ethanol and for LC-MS/MS analysis.…”
Section: Methodsmentioning
confidence: 99%
“…In spite of the signi cant effect of duration of feeding on condition factor (CF) and hepatosomatic index (HSI), there was no signi cant effect (p 0.05) of supplementation levels on CF and HSI of the sh. The nding did not correspond with that of a study by Enyidi (2017), who observed a decrease in HSI of African cat sh fed diet supplemented with 5% C. vulgaris. However, the nding corroborates with Kim et al (2013), who reported that medium-term feeding with diets whose shmeal was partially replaced with 15% Spirulina paci ca did not signi cantly affesct the HSI values of parrot sh (Oplegnathus fasciatus).…”
Section: Discussioncontrasting
confidence: 99%
“…Saadaoui et al (2021) observed that some microalgae have been used as food in livestock, poultry and aquaculture production due to their diverse nutritional properties. For example Chlorella vulgaris was used as a substitute for sh meal in feed for Clarias gariepinus (Enyidi 2017). In another study, El-Sheekh et al (2014) used Arthrospira platensis as feed for hybrid red tilapia (Oreochromis niloticus x Oreochromis mossambicus).…”
Section: Introductionmentioning
confidence: 99%